2022
DOI: 10.1002/cam4.4715
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with locally advanced head and neck squamous cell carcinoma undergoing concurrent chemoradiation withonce‐a‐weekversusonce‐every‐3‐weekscisplatin

Abstract: Introduction This trial was conducted to compare the efficacy of low dose once‐a‐week cisplatin and once‐every‐3‐weeks cisplatin with radiation in locally advanced head and neck squamous cell carcinoma (LAHNSCC). The current analysis focuses on the quality of life (QoL) of patients in this trial. Methods In this phase III randomized trial, patients with nonmetastatic LAHNSCC were randomized to receive cisplatin 30 mg/m2 once‐a‐week or 100 mg/m2 once every‐ 3‐weeks concurrently with radiotherapy. The primary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, Le et al did not find a difference in overall survival benefit in adding erlotinib to platinum–docetaxel chemotherapy vs placebo in patients amenable for surgical resection [ 39 ]. Therefore, as newer studies have suggested modification or de-escalation of treatment regimens to help reduce their impact on the patients’ QoL [ 7 ], it is of particular importance to have proper patient selection as some trials have failed to improve outcomes while trying to produce less toxicity [ 15 ]. For instance, patients that are HPV-positive have been shown to have a better response to chemoradiotherapy than patients that are HPV-negative [ 40 42 ].…”
Section: Significance Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Le et al did not find a difference in overall survival benefit in adding erlotinib to platinum–docetaxel chemotherapy vs placebo in patients amenable for surgical resection [ 39 ]. Therefore, as newer studies have suggested modification or de-escalation of treatment regimens to help reduce their impact on the patients’ QoL [ 7 ], it is of particular importance to have proper patient selection as some trials have failed to improve outcomes while trying to produce less toxicity [ 15 ]. For instance, patients that are HPV-positive have been shown to have a better response to chemoradiotherapy than patients that are HPV-negative [ 40 42 ].…”
Section: Significance Of Resultsmentioning
confidence: 99%
“…Many studies have shown that the addition of several non-invasive treatments may have a synergic effect in the overall survival of patients [ 4 6 ]. However, new studies have focused on modifying treatment regimens to not only increase survival, but to also reduce toxic effects [ 7 ]. Therefore, there is a fine line to decide if another combination of agents should be added or if the current regimen should be modified instead.…”
Section: Introductionmentioning
confidence: 99%
“…6 According to a previous study by Patel et al, they found that surgery with radiotherapy was associated with better mean survival (39.93 vs. 18.03 months, p < 0.0001) than radiotherapy alone in M1 HNC. 7 Unfortunately, previous studies have been mainly focused on the quality of life (QOL) in patients with advanced HNC, [8][9][10][11][12] but little has been performed to identify subgroups of patients who will benefit most from cancer-directed surgery (CDS) treatment. In addition, the standard treatment for patients with advanced nasopharyngeal carcinoma is radiotherapy or combined with chemotherapy, and surgery is not recommended.…”
Section: Introductionmentioning
confidence: 99%